Dynamic CT in patients with superficial temporal-middle cerebral artery anastomosis. - Takahashi, N; Kikuchi, H; Karasawa, J (American Journal of Neuroradiology, 1983)
Using dynamic computed tomographic (CT) scanning and an iodinated contrast material, changes in cerebral hemodynamics in cerebrovascular occlusive disease were studied before and after anastomosis of the superficial temporal artery and the middle cerebral artery. Because the iodinated contrast material is a nondiffusable indicator, it does not pass through the bloodbrain barrier. Thus, this method is capable of measuring the relative tissue blood flow (intravascular blood flow) but incapable of measuring the absolute cerebral blood flow. However, it does allow the three-dimensional measurement of cerebral hemodynamics by a simple procedure, and when the primarily clear brain structure seen with CT is considered, it is a very useful diagnostic method.